Extreme Contagion in Equity Markets - Yao, James (IMF Working Papers; Working Paper ;, 2002)
This study uses bivariate extremal dependence measures, based on the number of equity return co-exceedances in two markets, to quantify both negative and positive equity returns contagion in mature and emerging equity markets during the past decade. The results indicate (a) higher contagion for negative returns than for positive returns; (b) a secular increase in contagion in Latin America not matched in other regions; (c) global increases in contagion following the 1998 financial crises; and (d) that the use of simple correlations as a proxy for contagion could be misleading, as the former exhibit low correlation with extremal dependence measures of contagion.